Leverage dan Kebijakan Dividen sebagai Determinan Nilai Pasar Perusahaan - Lenni Yovita (Center for Accounting Development and Research (CARD) Program Studi Akuntansi – Fakultas Ekonomika dan Bisnis Universitas Kristen Satya Wacana, 2022)
The Covid-19 pandemic is a challenge for various companies, especially public companies, to continue to create company market value. This study aims to analyze the effect of Leverage and dividend policy, either partially or simultaneously on the creation of the company's market value. The sample used was 20 companies in the financial sectors that distributed dividends in the 2016-2020 period. By using multiple regression analysis technique of panel data, the results of the t-test hypothesis testing are obtained, namely both leverage (Debt To Equity Ratio) and dividend policy (Dividend Pay Out Ratio) each of which has a positive effect on the creation of the firm's market value (Market Value Added). Likewise, the results of the F test state that leverage and dividend policy have a simultaneous positive effect on the creation of the company's market value Keywords: Creating market firm value, dividend policy, leverage